Re: Instruction on the type of waterproofing treatment to be done in different location - BUCG-ABC Joint Venture (BUCG-ABC JV) (2023)
This record consists of general correspondence regarding the instruction on the type of waterproofing treatment to be done in different location of BRACU new campus project.